NOTARIAL LIABILITY FOR AUTHENTIC DEEDS DEGRADED INTO PRIVATE DEEDS AS A CONSEQUENCE OF FORMAL DEFECTS - Markus Gunawan (PT. Radja Intercontinental Publishing, 2023)
A notarial deed derives its status as an authentic instrument not from the office of the notary alone, but from strict compliance with the form prescribed by law. Where formal requirements under Law No. 2 of 2014 amending Law No. 30 of 2004 concerning the Position of Notary (UUJN) are breached, the instrument does not become void; it is degraded, retaining only the evidentiary force of a private deed. This study examines two problems: first, which formal breaches trigger degradation and what the precise legal consequence of that degradation is; second, the form, basis, and limits of notarial liability toward parties who suffer loss as a result. Using a normative juridical method with statutory, conceptual, and case approaches - including Supreme Court Decisions No. 351 PK/Pdt/2018 and No. 1266 K/Pdt/2022 - this article argues that degradation is a statutory evidentiary sanction rather than a nullity, and that liability does not follow automatically from it. Degradation establishes only the objective element of unlawfulness; the notary is civilly liable under Article 84 UUJN in conjunction with Article 1365 of the Indonesian Civil Code only where fault, actual loss, and adequate causation are additionally proven. The article further shows that Indonesian doctrine and practice frequently conflate degradation with liability, producing disproportionate outcomes, and proposes a three-tier framework distinguishing technical-formal breaches, substantive-formal breaches, and breaches induced by the parties themselves, coupled with mandatory professional indemnity coverage and a clearer evidentiary allocation before the Notary Supervisory Council.